The link between social risks factors with insufficient metabolic control and onset of T1D in children and adolescents in Russia - T. L. Kuraeva; A. V. Karpushkina; E. A. Andrianova; I. M. Valkova; T. V. Yakovleva; A. O. Emelyanov; E. A. Sechko; Z. G. Bezrukova; E. B. Khramova; Y. V. Girsh; I. V. Gunbina; V. A. Peterkova (Сахарный диабет)
Despite significant progress in the treatment of T1DM in children, achieving target levels of carbohydrate metabolism in children remains one of the most difficult tasks. The influence of the psychosocial state of the family on the ability to achieve metabolic compensation is becoming increasingly clear. However, the study of social risk factors in families with children with T1DM and their impact on metabolic control remains clearly insufficient.The purpose of the study is to determine social risk factors (SR) that are most typical for families of children with type 1 diabetes mellitus (T1DM) in our country and to analyze their relationship with compensation for T1DM based on a survey of parents.MATERIALS AND METHODS: The study was conducted in endocrinology departments of children’s hospitals and departments of medical and social care of children’s clinics in 4 regions - Vologda, Tyumen, Chelyabinsk regions and Khanty-Mansi Autonomous Okrug.A total of 325 respondents took part in the study. 1 group — experience of T1DM in children >1 year and poor metabolic control (level of glycated hemoglobin ((HbA1c) >7.5%) — 195 hours; 2 gr. — experience of T1DM in children >1 year and good metabolic control (HbA1c <7.5%) — 60 people. An additional group consisted of 73 patients with <1 year of experience of T1DM in children, regardless of metabolic control, in order to analyze the prevalence of social risk factors already in the 1st year of diabetes.RESULTS: In the overall group, HbA1c was 9.1% (4.9–17%). The five most common SR factors were a low level of parental education (lack of higher or secondary education), lack of a permanent job, raising a child alone, lack of support from loved ones, and income below the subsistence level.1 group (192 people). Average HbA1c level 9.8% (7.5–17%). Among the HR factors that significantly influence HbA1c levels, the level of education of parents, single parenting of a child, low family income and the number of children in the family were identified. The number of influencing social risk factors also has a negative impact on metabolic control.2nd group. (60 people). HbA1с — 6.6% (5.3%–7.3%). The prevalence of SR factors was significantly lower than in the previous group. The differences were significant for lack of higher education, single parenting, and low family income.3 gr. (73 people). HbA1c — 9.3% (4.9–15.1%, which may be due to the duration of diabetes less than 3 months in some children. After 3 months, the HbA1c level was 7.9% (4.8–13.4%). The list of SR factors practically coincides in composition and frequency with those in families of group 1. Thus, social difficulties that are not resolved in a timely manner aggravate the situation of the family and negatively affect the compensation of carbohydrate metabolism.CONCLUSION. We have identified the most significant factors of SR in families with children with T1DM in the Russian Federation. The deterioration of social conditions in the family is a factor that negatively affects the level of control of T1DM and the development of complications in the future. As a result, families with children with T1DM, especially with chronic decompensation, need assessment of SD factors and support from social services.